1992
DOI: 10.1038/ki.1992.304
|View full text |Cite
|
Sign up to set email alerts
|

Plasma level of lipoprotein Lp(a) is high in predialysis or hemodialysis, but not in CAPD

Abstract: Plasma Lp(a) lipoprotein level was determined in chronic renal failure (CRF) patients, 24 before initiation of dialysis, 18 undergoing hemodialysis, and 24 on continuous ambulatory peritoneal dialysis (CAPD). Eighteen healthy subjects were studied as controls. Median of Lp(a) level in both predialysis and dialysis patients was significantly increased: 23.5 mg/dl (range: 0 to 109) and 24.0 mg/dl (range: 1.4 to 90), respectively, as compared to healthy controls: 4.7 mg/dl (range: 1.8 to 27; P less than 0.001). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 8 publications
4
16
2
Order By: Relevance
“…The restoration of renal function after the graft leads rapidly to a significant decrease in Lp(a) concentrations in CAPD as in hemodialysis patients. Concerning CAPD patients, conflicting results were reported by our previous study [7]in which we had found normal Lp(a) values. The extremely wide range of Lp(a) plasma levels and its highly skewed distribution may explain this discrepancy particularly when the sample sizes are small.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The restoration of renal function after the graft leads rapidly to a significant decrease in Lp(a) concentrations in CAPD as in hemodialysis patients. Concerning CAPD patients, conflicting results were reported by our previous study [7]in which we had found normal Lp(a) values. The extremely wide range of Lp(a) plasma levels and its highly skewed distribution may explain this discrepancy particularly when the sample sizes are small.…”
Section: Discussioncontrasting
confidence: 41%
“…There are several reports of increased Lp(a) plasma concentrations in chronic renal failure patients [5, 6, 7]. After renal transplantation, results are not uniform, and it was concluded that renal function and/or cyclosporine therapy could influence the Lp(a) concentration [8].…”
Section: Introductionmentioning
confidence: 99%
“…8 Dialysis therapy may increases Lp(a) 10 or decreases Lp(a) level. 8,11 Some studies also reported that Lp(a) level did not vary before and after hemodialysis. 5,12 In our study we find elevated levels of Lp(a) in CRF patients with and without hemodialysis as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…6 Controversies exist regarding Lp(a) levels in CRF patients with and without hemodialysis. There are few studies that showed Lp(a) levels were elevated in CRF patients, 7,8,9 Lp(a) levels were elevated in hemodialysed patients, 10 Lp(a) levels were decreased after hemodialysis 8,11 and Lp(a) levels did not vary before and after hemodialysis. 5,12 With the implication of plasma lipids and lipoproteins in the pathogenesis of atherosclerosis and ischemic heart disease, it becomes worthwhile to study the behavior of various lipid fractions in CRF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Even though predialysis patients exhibit high serum Lp(a) levels [5, 6], there are sparse data with regard to serum Lp(a) concentrations in patients with mild/moderate renal failure [7, 8]. …”
Section: Introductionmentioning
confidence: 99%